2003
DOI: 10.1029/2003gl017396
|View full text |Cite
|
Sign up to set email alerts
|

Experimental observations of fracture dissolution: The role of Peclet number on evolving aperture variability

Abstract: [1] Dissolution of the surfaces of rock fractures can cause significant alteration of the fracture void space (aperture) and fracture permeability (k). Both surface reaction rates and transport of reactants within the fracture can limit local dissolution. We investigated the role of Peclet number (Pe), a measure of the relative importance of advective and diffusive transport of reactants, on fracture dissolution in two identical transparent analog fractures with different initial values of Pe (Pe o ). High-res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
139
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(148 citation statements)
references
References 10 publications
8
139
1
Order By: Relevance
“…[20]. Our results also agree with the numerical simulation and experimental results reported by several other authors [18,[21][22][23][24].…”
Section: Discussionsupporting
confidence: 83%
“…[20]. Our results also agree with the numerical simulation and experimental results reported by several other authors [18,[21][22][23][24].…”
Section: Discussionsupporting
confidence: 83%
“…In this regime a dissolution or precipitation front typically develops. The reaction front is often unstable in the dissolution case and leads to fingered dissolution channels, as documented in previous work on fractures [e.g., Hanna and Rajaram, 1998;Durham et al, 2001;Detwiler et al, 2003;Szymczak and Ladd, 2004;Detwiler and Rajaram, 2007]. Natural spatial variations in fracture apertures aid the initiation of unstable finger growth [Cheung and Rajaram, 2002].…”
Section: Introductionmentioning
confidence: 87%
“…Thus, solute transport in the fracture was controlled by advection in all experiments (e.g., Detwiler et al, 2000) regardless of the composition of the solutions. Earlier studies show a certain correlation between distinct dissolution patterns in fractured cores and Pe numbers (Detwiler et al, 2003;Szymczak and Ladd, 2009;Elkhoury et al, 2013;Garcia-Rios et al, 2015). Elkhoury et al (2013) reported that at low Pe, development of dissolution instabilities in fractured vuggy limestone cores led to face dissolution, intermediate Pe gave rise to large-scale channels, and a high Pe regime led to uniform dissolution along the fracture.…”
Section: Tablementioning
confidence: 99%